Partial chest wall radiation therapy for positive or close surgical margins after modified radical mastectomy for breast cancer without lymph node metastasis. Issue 1 (5th November 2019) - Ishibashi, Naoya; Nishimaki, Haruna; Maebayashi, Toshiya; Adachi, Keita; Sakurai, Kenichi; Masuda, Shinobu; Hata, Masaharu; Okada, Masahiro
Abstract: Aim: Whole‐breast radiation therapy after breast‐conserving surgery can control local recurrence with a long‐term survival rate equivalent to that of radical mastectomy for patients with early breast cancer. However, the significance of radiation therapy for patients with positive/close margins after mastectomy remains controversial. Following radical mastectomy, no residual breast parenchyma remains, and thus radiation therapy of the entire chest wall may represent overtreatment in the patients, especially those without lymph node metastasis ( N 0). We therefore implemented partial chest wall radiation therapy for patients with N 0 breast cancer and positive and/or close margins after mastectomy. Methods: A total of 22 patients with N 0 status but positive/close margins underwent partial chest wall radiation therapy to irradiate the predetermined clinical target volume, which had margins of at least 2 cm medial, lateral, superior, and inferior to the primary tumor bed. With reference to chest wall thickness, 4‐10‐MV photons or 5‐8‐MeV electrons with/without a bolus were delivered. The total dose was 50‐66 Gy. We compared the results with those from 18 nonradiation therapy patients using Pearson's χ 2 test. Results: All patients in the partial chest wall radiation therapy group achieved good local control despite having a significantly higher proportion of positive margins (77.3%) compared with the nonradiation therapy group (27.8%) ( P = 0.002). Both groups showed 100% recurrence‐ and disease‐free survival. Conclusion: Partial chest wall radiation therapy may offer recurrence‐ and disease‐free survival without local recurrence in N 0 mastectomy patients with positive/close surgical margins.